Electrical properties of amino acid substituted novel cinnamic acid compounds - GÖRGÜLÜ, AHMET ORHAN (My University, 2020)
Amino acid conjugates are combinations of one or more compounds, at least one of them active in terms of biological, pharmacological or physical. In this work, some novel amino acid conjugates, four different aldehydes (Pyrene, Naphthalene, Phenanthrene and Phenyl benzyl) have been chosen and from these initial materials four different amino acid conjugates were synthesized. The compounds from initial steps to final steps have been characterized by 1H and 13C APT NMR spectroscopy. The dielectric measurements were done by QuadTech 7600 LRC impedance analyzer. The dielectric constant (ε′) dielectric loss (ε’’) and ac conductivity (σ) values of amino acid conjugates in the frequency of 1 kHz and at 25 °C. The results show that the increase in conjugation affect the dielectric constant and conductivity.
Keywords: Kimya; Analitik Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Spektroskopi; İnorganik Kimya; Temel Bilimler; Chemistry; Analytical Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Spectroscopy; Inorganic Chemistry; Natural Sciences; Temel Bilimler (SCI); KİMYA, İNORGANİK VE NÜKLEER; KİMYA, ANALİTİK; SPEKTROSKOPİ; KİMYA, ORGANİK; Natural Sciences (SCI); CHEMISTRY; CHEMISTRY, INORGANIC & NUCLEAR; CHEMISTRY, ANALYTICAL; SPECTROSCOPY; CHEMISTRY, ORGANIC; Fizik Bilimleri; Organik Kimya; İnorganik kimya; Physical Sciences; Organic Chemistry; Amino acid; Cinnamic acid; Conductivity /synthesis; Dielectric